Introducing an Interdisciplinary Frontier to Judging, Emotion and Emotion Work - Anleu, Sharyn R. (2019)
This special issue of Oñati Socio-Legal Series, titled Judging, Emotion and Emotion Work, is the result of presentations and discussions during an interdisciplinary workshop at the International Institute for the Sociology of Law (IISL) held in May 2018. This issue builds on the growing critique of the dispassionate ideal of judicial work, combining original theoretical insights with imaginative empirical analyses to extend the understanding of emotion in judging. Fifteen articles are presented in four themes: Theoretical, cultural and historical perspectives; Tensions of the dispassionate ideal; Social dynamics of emotion in judging; and Research methods, empirical insights and [changing] judicial practice. The international diversity of contributions recognises similarities and differences in the structure and organization of courts and the judiciary, and socio-cultural variations in emotional experience and expression